Global law - Jiménez Alemán, Ángel Aday (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
The legal globalization and the generation of a global law -still in early stages- are expressions of the globalization as a multifaceted phenomenon, and understood as the acceleration and merging of social relationships until the constitution of a whole organic body. In spite of the overwhelming literature related to globalization, we have not go beyond a prescientific stage, especially in the legal sciences. Law has been affected as well by the de-territorialisation, acceleration and intensification of social relationships, emerging a new disordered and multiple reality. The legal globalization has been revealing itself by, among other facts, the diffusion and adoption of similar legal institutions in different legal orders, or even their integration, along with the transferring of power to jurisdictional organs in a constant dialogue. At the same time, we have been witnesses of the proliferation of transnational legal orders. From entities that are not the nation-states, they regulate social relationships beyond the jurisdiction of the nation-state, coming up the question about the existence of a global legal order. doi: http://dx.doi.org/10.20318/eunomia.2016.3290